Slag erosion-resistant coating for periclase-magnesia-aluminum spinel brick. Issue 22 (15th November 2021) - Jia, Xiaodong; Tian, Lin; Mao, Shuo; Zhou, Xiaolei; Chen, Shujiang; Li, Guohua
Abstract: The magnesia-carbon bricks are used at the ladle slag line adds carbon to molten steel and thus has an adverse effect on the smelting process. Steel production enterprises hope to remove carbon from the ladle slag line. This study presents a Silica sol (SS)–magnesium aluminate spinel(MA) coating that can be applied to the surfaces of periclase–MA spinel brick (spinel brick) to improve their slag erosion resistance, facilitating the elimination of carbon from the ladle slag line. The slag corrosion resistance mechanism of a spinel brick covered with the SS–MA coating was analyzed through scanning electron microscopy and simulation using FactSage software. The results show that increasing the SS content (CSS ) led to the formation of fine cracks during the coating-drying process and was detrimental to the slag erosion resistance of the coating. The optimum CSS was 20%. In the high-temperature slag erosion experiment, the MA in the coating was capable of forming solid solutions with Fe and Mn in the slag, and the nano-SiO2 in the coating interacted with the slag, increasing the viscosity of the slag and reducing its penetration. In addition, the presence of the coating extended the penetration path of the slag and reduced the contact area between the slag and the spinel brick and their chances to undergo chemical reactions, thereby protecting the spinel brick from slag erosion. The coated spinel bricks outperformed the magnesia-carbon brick in terms of slag erosion resistance, providing a basis for selecting carbon-free refractory materials for the ladle slag line.